Biodata Vol. I (Volume 40) (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2013)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Horsemanship; Newspapers; Archives; Newspaper Article; Art Exhibition; Flyer; Iwalewahaus; Cultural Centre